Congenital Extrahepatic Portosystemic Deviation in a Mixed-Breed Dog - de Oliveira Cavalcanti, Ellen Bethânia; Baioto, Gustavo Cancian; Marcolongo-Pereira, Clairton; Carlos de Souza, Mayara Coutinho; Rassele, Alice Corrêa; dos Santos Horta, Rodrigo (Acta Scientiae Veterinariae, 2019)
Background: Portosystemic deviation (PSD) is a congenital or acquired vascular anomaly that allows an abnormal blood flow from the portal vein directly to the systemic circulation. This liver by-pass avoids hepatic metabolism of several toxins. Congenital PSDs are usually solitary and extra-hepatic, with a high incidence in pure-breed dogs. Acquired PSDs are usually multiple and occur as a consequence of portal hypertension. Surgery is the definitive treatment. Clinicians and surgeons may present difficulties in the propaedeutic of animals with PSD. This paper aims at reporting a successful surgical treatment of a solitary extra-hepatic congenital PSD in a mixed-breed dog. Case: A 7-month-old mixed-breed dog, female, spayed, weighing 8 kg, was presented with a history of sudden syncope after feeding. Complementary exams revealed normocytic hypochromic anaemia, hypoalbuminemia and increased alanine aminotransferase and alkaline phosphatase. Abdominal ultrasound revealed an anomalous vessel inserted in the caudal cava vein, compatible with a congenital extra-hepatic PSD. Computed tomography revealed the anomalous vessel, with 1,1 cm of diameter, originated from the cranial mesenteric vein and it inserted in the cranial margin of the caudal cava vein. A medical support was started with hydration, metronidazole, lactulose, probiotic and Hepatic diet. After 15 days the dog was submitted to surgery and a 5 mm ameroid constrictor ring was placed to gradually close the anomalous vessel. The dog recovered well and an abdominal ultrasound was repeated after 30 days, showing the ameroid constrictor ring ring in the left cranial abdominal region, occluding the PSD close to its insertion in the caudal cava vein. The patient was followed up for more than three years, gained weight and presented a healthy normal life. Discussion: Although PSD is more often diagnosed in pure-breed dogs, this paper reports a case in a mixed-breed dog. However clinical signs and the age of onset were compatible with this pathology. Dogs with PSD may present neurological, gastrointestinal and urinary disorders, related to failure of the detoxification process and toxin by-pass to the systemic circulation. Young dogs are usually presented overdue underdevelopment, reduced body height or weight loss as described in this report. Hepatic encephalopathy is a result of the production of ammonia and several other toxins, which escapes hepatic metabolism, and once they remain liposoluble, they are able to cross-pass the blood-brain barrier and produce the neurological signs, which might be more pronounced after feeding, as in the reported case, although this dog presented only mild neurological signs. The haematological and biochemical findings in the dog of this report were also compatible with PSD. Hypoglycemia, hypocholesterolemia, increased of bile acids and serum ammonia may also be present but they were not demonstrated in this case. Abdominal ultrasound was able to identify the anomalous extra-hepatic vessel which was precisely described by computed tomography, which allower surgical planning. Medical support is recommended for the patient´s clinical estabilization, as performed in this case. Surgery is the treatment of choice for congenital solitary PSD, as in the reported case, and placement of the ameroid constrictor is the most employed technique, as performed. Patient´s improvement starts in the day after surgery and it is completed within a couple months. The patient of this report did not present any complications in the postoperative period and for more than three years, showing total remission of the clinical signs and good life´s quality.